2014
DOI: 10.3389/fnbeh.2014.00165
|View full text |Cite
|
Sign up to set email alerts
|

Detaching from the negative by reappraisal: the role of right superior frontal gyrus (BA9/32)

Abstract: The ability to reappraise the emotional impact of events is related to long-term mental health. Self-focused reappraisal (REAPPself), i.e., reducing the personal relevance of the negative events, has been previously associated with neural activity in regions near right medial prefrontal cortex, but rarely investigated among brain-damaged individuals. Thus, we aimed to examine the REAPPself ability of brain-damaged patients and healthy controls considering structural atrophies and gray matter intensities, respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
48
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 116 publications
(168 reference statements)
4
48
1
Order By: Relevance
“…Aron et al (2004) argues that the right VLPFC plays a critical role in cognitive inhibition. Cognitive inhibition is a component of executive control that can be localized to the right inferior frontal gyrus, specifically the pars opercularis (Molnar-Szakacs et al, 2005; Falquez et al, 2014). Inhibition can be defined as the suppression of inappropriate responses (Aron et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aron et al (2004) argues that the right VLPFC plays a critical role in cognitive inhibition. Cognitive inhibition is a component of executive control that can be localized to the right inferior frontal gyrus, specifically the pars opercularis (Molnar-Szakacs et al, 2005; Falquez et al, 2014). Inhibition can be defined as the suppression of inappropriate responses (Aron et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The SFG is thought to contribute to higher cognitive functions, and play a particularly important role in working memory (Boisgueheneuc et al, 2006). The functional anatomical region referred to as the DLPFC (BA9) overlaps structurally, in part, with SFG (Owen et al, 2005; Falquez et al, 2014). …”
Section: Discussionmentioning
confidence: 99%
“…The function of this part of SFG is not well studied, but it shows consistent functional coupling with nodes of the default mode network (74, 17, 75, 76). Moreover, introspective tasks increase activity specifically in this part of SFG, with activity extending medially into BA32 (77), while damage to SFG and BA32 correlates with impairment in re-appraising the personal relevance of negative events (78). Interestingly, this part of SFG has also been implicated in expressions of positive affect such as laughter (79) and humor (80) important for self-centered re-appraisal.…”
Section: Discussionmentioning
confidence: 99%
“…Emotion regulation through reappraisal has been investigated in many functional neuroimaging studies, which showed the involvement of prefrontal areas (including structural changes; Falquez et al, 2014;Giuliani, Drabant, & Gross, 2011) and the down-regulation of limbic structures such as the amygdala (Buhle et al, 2014;Diekhof et al, Fig. 2 Neural correlates of emotion regulation. Neural correlates of reappraisal (yellow circles) and suppression (red circles) previously reported in three studies that have compared reappraisal and suppression (Goldin et al, 2008;Hayes et al, 2010;Vanderhasselt et al, 2012).…”
Section: Maladaptive Consequences Of Cognitive Controlmentioning
confidence: 99%